TINJAUAN ASPEK KESEJAHTERAAN HEWAN PADA SAPI YANG DIPOTONG DI RUMAH PEMOTONGAN HEWAN KOTAMADYA BANDA ACEH (Study of the Animal Welfare Aspect on Cattle Slaughtered in Slaughter house in Banda Aceh) - Yudha Bhaskara; Mulyadi Adam; Idawati Nasution; Triva Murtina Lubis; Teuku Armansyah; Muhammad Hasan (Jurnal Medika Veterinaria, 2015)
This study was conducted to obtain the information about animal welfare on cattle slaughtered in Slaughterhouse in Banda Aceh. The animal welfare parameter was observed related to the transport aspect, shelter aspect, and slaughter aspect. The three aspects compared to the recommendation of Meat Livestock Australia (MLA) and Indonesian National Standard 02-4509-1998. Method used to determine the animal welfare was scoring evaluation. The result of study showed that transport aspect get 20 score with a percentage of 50% which categorized as sufficient. Shelter aspect get 33 score with percentage of 82,5% which categorized as good, and slaughter aspect get 32 score with percentage of 80% which categorized as good. Based on scoring evaluation of shelter aspect and slaughter aspect, the animal welfare of cattle slaughtered in Slaughter house in Banda Aceh is considered good, meanwhile the transport aspect is considered sufficient.Key words: animal welfare, cattle, slaughterhouse